Key aroma compounds in Chinese fried food of youtiao - Du, Wenbin; Zhao, Mengyao; Zhen, Dawei; Tan, Jia; Wang, Tianze; Xie, Jianchun (Flavour and fragrance journal, 2020)
Key aroma compounds in Chinese popular fried food of youtiao were characterized by solvent assisted flavor evaporation combined with gas chromatography‐mass spectrometry (GC‐MS) and aroma extract dilution analysis of gas chromatography‐olfactometry (AEDA/GC‐O), quantitation, and aroma recombination and omission. Four samples of youtiao fried with sunflower oil, soybean oil, rapeseed oil, and palm oil, respectively, differing in fatty acid composition, were selected to be investigated. A total of thirty‐five odorants were identified, among which twenty‐two odorants were quantitated by aid of authentic chemicals and with correction of recovery coefficients. Differences in odorants composition and aroma profile were observed among the four samples of youtiao fried with different oils. However, it was demonstrated in common thirteen compounds; that is, 3‐hydroxy‐2‐butanone, 3‐methylbutanal, furfural, 3‐(methylthio)propanal, 2‐furfurylthiol, phenylacetaldehyde, 2,5‐dimethyl‐4‐hydroxy‐3(2H)‐furanone, 2‐ethyl‐3,5‐dimethylpyrazine, 3‐ethyl‐2,5‐dimethylpyrazine, (E,E)‐2,4‐decadienal, 1‐octen‐3‐ol, (E,Z)‐2,6‐nonadienal, and (E)‐2‐nonenal contributed significantly to youtiao aroma. The work can provide some guidance to maintain the preferred youtiao flavor when modifying its preparation technology for safety concerns. Analyze common and key odorants in youtiao fried with four oils by GC‐MS‐O and aroma recombination.